SPIRITUAL INNER “SELF” AS A SELF-CONTROL MECHANISM TO TRIGGER HUMAN GOVERNANCE - Nor Azmi Ramli; Ainul Abdul-Mohsin (Journal of Islamic, Social, Economics and Development, 2024)
In the light of numerous corporate disasters, the external control mechanism, either for self-regulation or direct control created by a rule-based governance structure as a philosophy, has proven to be ineffective. Promoting internal drive with consciousness from the inner side is essential for creating a governance structure for governing humans. Humans, on the other hand, govern the organisation. The phenomenon of corruption is global, and the Human Governance viewpoint has been suggested as a way of controlling corruption. However, it does not go into detail about human spiritual anatomy in explaining the behaviour of integrity or corruption. This research is qualitative in nature, and the findings suggest that the driving force behind the behaviour of integrity is the Soul-at-Peace due to the virtue characters. What encapsulates the taxonomy of virtue characters is the Human Governance philosophy. Conversely, the driving force behind the behaviour of corruption is the Inciting Soul due to the vice characters. The novelty of this research is that it uses the human model, which consists of “at once the physical and the non-physical dimensions.” Human Governance is the inner workings of being human that influence the decisions about upholding integrity or committing corruption.